The biology of coral reefs - Sheppard, Charles (Charles R. C.); Davy, Simon K.; Pilling, Graham M. (Oxford University Press, 2009)
A concise but comprehensive introduction to the biology of coral reefs, providing an overview of the ecology of coral reefs and their functioning, and the biology of their major species groups. The responses to modern environmental pressures, climate change, and use of their resources is also described.